Предмет: Алгебра,
автор: imirkulova
дакажите тождество первый и второй пример
Приложения:
Ответы
Автор ответа:
0
1) a/(a-1)*(1-a)/(a-2a^2+a-a^2)=-a/(2a-3a^2)=a/a(3a-2)=1/(3a-2)
2) ((a-b/(a(a+b)-a/b(a+b)):(1/(a+b)-b^2/a(b^2-a^2))=
=(ab-a^2-b^2)/ab(a+b):(ab-a^2-b^2)/a(b^2-a^2)=(b^2-a^2)/(b(a+b)=b-a/b
2) ((a-b/(a(a+b)-a/b(a+b)):(1/(a+b)-b^2/a(b^2-a^2))=
=(ab-a^2-b^2)/ab(a+b):(ab-a^2-b^2)/a(b^2-a^2)=(b^2-a^2)/(b(a+b)=b-a/b
Похожие вопросы
Предмет: Английский язык,
автор: LINCENTTTIA
Предмет: Психология,
автор: 2moloko2
Предмет: Русский язык,
автор: Hulcksmashers
Предмет: Геометрия,
автор: moOntik